Optimalisasi Pengawasan Pelayanan Perizinan Berusaha Terintegrasi Berdasarkan Prinsip Keadilan Berbasis Environmental Ethics di Kota Semarang - Helen Alisya (Jurnal Hukum Lex Generalis, 2025)
The implementation of business licensing in Semarang City still faces obstacles due to the lack of integration between agencies, limited human resources, and low public awareness and understanding of business legality. The less than optimal licensing service in Semarang has resulted in industrialization that is detrimental to the rights of the community in terms of the environment. Therefore, supervision of business licensing must be optimized based on indicators of the principle of justice based on environmental ethics which can be implemented with a pattern of feed forward control, concurrent control, feedback control and preventive and repressive supervision.